Governed by the cycle : direct and inverted interest-rate sensitivity of emerging market corporate debt - Gubareva, Mariya (2016)
An innovative approach to quantify interest rate sensitivities of emerging market corporates is proposed. Our focus is centered at price sensitivity of modeled investment grade and high yield portfolios to changes in the present value of modeled portfolios composed of safe-haven assets, which define risk-free interest rates. Our methodology is based on blended yield indexes. Modeled investment horizons are always kept above one year thus allowing to derive empirical implications for practical strategies of interest rate risk management in the banking book. As our study spans over the period 2002 – 2015, it covers interest rate sensitivity of assets under the pre-crisis, crisis, and post-crisis phases of the economic cycles. We demonstrate that the emerging market corporate bonds both, investment grade and high yield types, depending on the phase of a business cycle exhibit diverse regimes of sensitivity to interest rate changes. We observe switching from a direct positive sensitivity under the normal pre-crisis market conditions to an inverted negative sensitivity during distressed turmoil of the recent financial crisis, and than back to direct positive but weaker sensitivity under new normal post-crisis conjuncture. Our unusual blended yield-based approach allows us to present theoretical explanations of such phenomena from economics point of view and helps us to solve an old controversy regarding positive or negative responses of credit spreads to interest rates. We present numerical quantification of sensitivities, which corroborate with our conclusion that hedging of interest rate risk ought to be a dynamic process linked to the phases of business cycles as we evidence a binary-like behavior of interest rate sensitivities along the economic time. Our findings allow banks and financial institutions for approaching downside risk management and optimizing economic capital under Basel III regulatory capital rules.